Analisis Readiness for Change Dalam Implementasi Sistem Perkantoran Digital Pada Instansi Komando Operasi Udara I (KOOPSUD I) - Tia Almamega; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the readiness for change in the implementation of a digital office system at Komando Operasi Udara I (KOOPSUD I) Institution. A qualitative method with a case study approach was employed to provide a comprehensive understanding of the organization's and employees’ preparedness for digital transformation. The unit of analysis includes employees at various management levels who are directly involved in the implementation process. Data were collected through observation, in-depth interviews, focus group discussions, and document analysis. The findings indicate that the level of readiness for change is moderate. While infrastructure and technology are considered adequate, gaps remain in employees’ digital competencies and organizational culture. Key challenges include resistance to change among senior staff, limited comprehensive digital training, and misalignment between management policies and on-the-ground implementation. Recommended strategies to enhance readiness include strengthening continuous digital training programs, appointing change agents in each unit, developing a more structured implementation roadmap, and conducting regular evaluations of progress. This study contributes to the understanding of critical factors influencing organizational readiness in the public sector for digital system adoption and can serve as a reference for other institutions planning similar transformations.